Framing the Body and the Body of Frame: Item songs in popular Hindi cinema - Kaur, Ravneet (Acta Orientalia Vilnensia, 2011)
University of DelhiThe basic framework of this paper is to deliberate upon the emergence of item songs as a reinstatement of the dominance of the ‘song and dance sequences’ in popular Hindi cinema, and its inferences as a sub-text in contemporary cultural forms. While doing so, the paper argues that the transition in consumption and the circulation/distribution of Hindi film songs, and other visual/ audio media has affectively facilitated the course. In the given context, the paper further attempts to address shifts in the filmic techniques that have consistently regulated the production of such songs, revealing a spectrum of negotiations between and among the ‘body’, ‘performance’, and ‘frame’, with which the spectator becomes familiarized over a series of visual/ audio leaps that have taken place in the traditional media forms like that of television and in newer forms like the internet.